2019
DOI: 10.1108/jea-05-2019-0089
|View full text |Cite
|
Sign up to set email alerts
|

Supporting principal supervisors: what really matters?

Abstract: Purpose Districts across the country are calling on their principal supervisors to shift from mainly focusing on operations and compliance to dedicating their time to help principals grow as instructional leaders. Learning theory elaborates that such support for principals demands that supervisors take a teaching-and-learning approach – which the authors define as consistently using particular strategies that are characteristic of high quality teachers and mentors across various apprenticeship settings – to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
46
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 31 publications
5
46
1
4
Order By: Relevance
“…Authentic learning opportunities, like problem-based learning and on-the-job expert coaching/mentoring, are also examples of meaningful principal development activities that can be coordinated by school districts (Darling-Hammond et al, 2007; Stucher et al, 2017). Though evidence is still emerging, early research suggests that principal supervisors can play a critical role in development, particularly in the areas of racial equity (Rigby et al, 2019) and instructional improvement (Honig, 2012; Honig & Rainey, 2019; Thessin & Louis, 2019). Furthermore, at least one study has pointed to a specific area where principals might benefit from additional training and support to foster competence—using data to assess teacher effectiveness and to make hiring decisions (Cannata et al, 2017).…”
Section: District Support For Leader Learning Development and Successmentioning
confidence: 99%
See 2 more Smart Citations
“…Authentic learning opportunities, like problem-based learning and on-the-job expert coaching/mentoring, are also examples of meaningful principal development activities that can be coordinated by school districts (Darling-Hammond et al, 2007; Stucher et al, 2017). Though evidence is still emerging, early research suggests that principal supervisors can play a critical role in development, particularly in the areas of racial equity (Rigby et al, 2019) and instructional improvement (Honig, 2012; Honig & Rainey, 2019; Thessin & Louis, 2019). Furthermore, at least one study has pointed to a specific area where principals might benefit from additional training and support to foster competence—using data to assess teacher effectiveness and to make hiring decisions (Cannata et al, 2017).…”
Section: District Support For Leader Learning Development and Successmentioning
confidence: 99%
“…Furthermore, the advent of intermediary principal supervisory roles has precipitated increased study of these positions as potentially important vehicles for building principal efficacy as instructional leaders (Honig & Rainey, 2019; Thessin & Louis, 2019). In a study of three districts, Honig (2012) found that high variation in Instructional Leadership Director practices with respect to self-efficacy emphasized the importance of several key practices: (a) the degree to which principal supervisors worked to inculcate in principals the value of principal instructional leadership; (b) the use of modeling and its role in forging meaningful, productive relationships with principals; and (c) the use of tools as a basis for having challenging conversations and serving as information “brokers” (i.e., providing principals with connections to external resources).…”
Section: District Support For Leader Learning Development and Successmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that they became "more engaged in coaching, mentoring and partnering with the specific goal of improving student achievement" (Browne-Ferrigno and Allen, 2006;Clarke and Wildy, 2011;Johnson and Chrispeels, 2010;Leithwood, 2010). The same processes are reported as taking place in other localities of the USA as well as in Canada, Australia and Scotland (Leithwood et al, 2019;Wilkinson et al, 2019;Honig and Rainey, 2019;Chapman, 2019). The changing role of principal supervision has triggered various approaches and efforts to achieving success.…”
mentioning
confidence: 99%
“…their central o ces as engines of educational equity (Honig, 2012;Honig & Rainey, 2014, 2019, 2020Honig, Venkateswaran, & McNeil, 2017). As part of their e orts, leaders in all these districts took concrete steps to focus principal supervision on supporting principals' growth as instructional leaders, but they ended up with quite di erent results.…”
mentioning
confidence: 99%